Application of econometric model for water economy management - Ramczyk, Marek (International Conference “Environmental Engineering”, 2017)
The econometric model can be a precise instrument for the analysis of the impact of the natural environmental degradation on the fishing economy. This paper aims at analysing the influence of the water quality changes in Charzykowskie Lake on the fishing economy. The economic-ecological models have been constructed, explaining the changes of economic effects of the lake fishery in the conditions of an increasing water pollution in the hypolimnion on the example of the catch of Rutilus rutilus, Blicca bjoerkna, Coregonus lavaretus, Anguilla anguilla and Esox lucius in Charzykowskie Lake. Performed empirical research focuses on the influence of the environmental factors on the size of fish catch. Calculations and analysis show clearly that even though the habitat factors have an influence on the catch size of each studied fish species, they do it with different intensity and in various combinations. Both, lake water quality and climate factors changes, cause measurable effects on fishing industry of Charzykowskie Lake. Among the examined Rutilus rutilus and Blicca bjoerkna, Blicca bjoerkna has the highest high environmental requirements regarding the water quality. Empirical calculations showed as well that Coregonus lavaretus has considerably higher water cleanness requirements than Rutilus rutilus and Blicca bjoerkna. While considering Rutilus rutilus and Blicca bjoerkna, most water characteristics still rather stimulate a development of these species, but when it comes to Coregonus lavaretus, in general they suppress its development. The model has also proved quite high habitat requirements for Anquilla anquilla and correctness of the thesis that Esox lucius avoids polluted water. Climatic factors influence is significant for the endogenous variables. The above prejudges the itineration of Rutilus rutilus, Blicca bjoerkna, Coregonus lavaretus, Anquilla anquilla and Esox lucius catch in Charzykowskie Lake. The results of the modelling can be used in managing the fishing economy of the lake.
Keywords: econometric model; water economy; lake water pollution; managing